What is a Social Outburst? A Conceptual Proposal Based on its Size and Level of Organization - Chávez Angeles, Noelia Solange (2026)
Although the term social outburst has become central to describing the large-scale mobilizations that have shaped Latin America in recent years, academic usage still lacks a parsimonious and widely accepted definition. Recent literature characterizes these episodes through attributes such as massiveness, spontaneity, lack of coordination, ephemerality, or violence. However, these approaches often accumulate features without providing analytical criteria that clearly distinguish outbursts from other forms of contentious collective action. This article proposes a minimalist definition based on two structural criteria, size and organization, that allows for distinguishing social outbursts from social movements, strikes, and riots. The proposal is illustrated with regional examples that demonstrate its capacity to distinguish social outbursts from other forms of contentious collective action and is further developed through a comparative analysis of three recent episodes from Chile, Colombia, and Peru. The article concludes by discussing the scope and limits of this definition for future research on contentious politics.